Ocupação antrópica nas Áreas de Preservação Permanente APPs urbanas : estudo das áreas lindeiras aos córregos dos Bagres, Cubatão e Espraiado em Franca/SP - Felicio, Bruna da Cunha (2007)
The analysis and discussion about anthropic occupation of Permanent Preservation Areas along urban water streams constitute the central part of this work. Initially was tried to understand how human beings dominate space and how this domination is degrading the life quality of Man himself through times. Then, through the studies of occupation of Permanent Preservation Areas of Bagres, Cubatão and Espraiado streams in Franca/SP, we tried to explain the problems of Permanent Preservation Areas, as well as identify along with the legal aspects the critical situation of the treatment given to these areas by the society and the government.